1998
DOI: 10.1074/jbc.273.36.23433
|View full text |Cite
|
Sign up to set email alerts
|

Different Molecular Mechanisms for Rho Family GTPase-dependent, Ca2+-independent Contraction of Smooth Muscle

Abstract: Abnormal smooth muscle contraction may contribute to diseases such as asthma and hypertension. Alterations to myosin light chain kinase or phosphatase change the phosphorylation level of the 20-kDa myosin regulatory light chain (MRLC), increasing Ca 2؉ sensitivity and basal tone. One Rho family GTPase-dependent kinase, Rho-associated kinase (ROK or p160 ROCK ) can induce Ca 2؉-independent contraction of Triton-skinned smooth muscle by phosphorylating MRLC and/or myosin light chain phosphatase. We show that ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 37 publications
2
100
0
Order By: Relevance
“…6). As reported previously, GST-Pak 3 is susceptible to degradation (33). The resulting fusion protein reacted with the pPak(AL) Ab and the pPak 1/2(Ser 144/141 ) Ab (Figs.…”
Section: Dephosphorylation Of Gst-pak 3 By Ppsmentioning
confidence: 88%
“…6). As reported previously, GST-Pak 3 is susceptible to degradation (33). The resulting fusion protein reacted with the pPak(AL) Ab and the pPak 1/2(Ser 144/141 ) Ab (Figs.…”
Section: Dephosphorylation Of Gst-pak 3 By Ppsmentioning
confidence: 88%
“…At high concentrations of PDGF, the inhibition by PI3-kinase inhibitors appeared to be overcome, at least partially. Interestingly, smooth muscle contraction that is independent of MLC phosphorylation has been reported to involve the protein kinase PAK (33), and PAK has been implicated in cell membrane ruffling as well (34 -36). While our studies were in progress, two other laboratories also showed that blocking PI3-kinase inhibits PDGF-dependent collagen matrix contraction (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Because PAK directly phosphorylates MLC on serine 19 (Ramos et al, 1997;Chew et al, 1998;Van Eyk et al, 1998), we investigated the possibility that MLC acts downstream of PAK to mediate its effect on spine morphogenesis and excitatory synapse formation. We first examined the localization of activated MLC in hippocampal neurons.…”
Section: Active Mlc Localizes To Dendritic Spinesmentioning
confidence: 99%